Acute and chronic toxicity assessment of benzylpenicillin G residue in heat-treated animal food products. (July 2018) - Cui, Cheng; Zhang, Xiang; Wang, Yang; Lu, Shiying; Lu, Huijun; Hui, Qi; Ahmad, Waqas; Cai, Yan; Liu, Xilin; Liu, Lingjiu; Shi, Fengfeng; Liu, Yanyan; et al.
Abstract: The current level of penicillin use and its persisting residue in livestock is potentially concerning; the toxicity of penicillin residue in heat-treated animal food products (HAFP) is yet to be elucidated. In this study, the acute and chronic toxicity of benzylpenicillin G (BPG) residue in HAFP was investigated in a mouse model. The calculated LD50 of BPG heated to cooking temperature (BPHCT) was 933.04 mg kg −1 [b.w.] intraperitoneally corresponding to 3.75 times lower than its prototype. Mice fed on the experimental diet containing heat-treated beef with high BPG levels for 6 months displayed a reduction in body weight and altered serum values indicating for liver and renal function. Further, the organ ratios of intestinal and spleen were increased. Histopathological changes were observed in the liver, lung and parenchyma testis tissue. BPHCT residue induced sperm aberration and micronucleated polychromatic erythrocytes formation. Present results indicate that prolonged exposure of BPHCT at higher residue levels might have an impact on public health. Importantly the toxic concentrations of BPHCT are relatively high compared with levels that would result from the degradation of antibiotic residues in meat from animals that have received a therapeutic dose of BPG. Graphical abstract: Image 1 Highlights: The toxicity of BPHCT was 3.75 times higher than the prototype of BPG. There are five major degradation products of BPHCT. Long time exposure with high dose of BPHCT residue might cause sperm toxicity and genotoxicity. Over dosage of BPHCT residue may potentially result in hepatotoxicity, pulmonary toxicity and testicular damage.